2023
DOI: 10.1186/s12866-023-02910-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial hazard identification and exposure assessment of raw milk consumption in Jimma zone, South West Ethiopia

Abstract: Background Raw milk may contain pathogenic microorganism that can sometimes fatally affect the health of consumers. However, risks related to raw milk consumption in Southwest Ethiopia are not well studied. The aim of this study was to evaluate the presence of five target pathogenic bacteria including Escherichia coli O157:H7, Salmonella enterica Typhimurium, Staphylococcus aureus, Listeria monocytogenes, and Campylobacter jejuni in raw milk and to assess exposure associated with the consumptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The microbial agents mainly coliform, i.e., E. coli, S. aureus, Salmonella spp., Campylobacter spp. and Listeria monocytogenes are microbes that potentially contaminate foods, and pose public health threat (Osafo et al 2022;Rafiq et al 2022;Gume et al 2023). The present study was undertaken based on the law of the Republic of Indonesia # 7 of 1996 concerning food that food of animal products must meet the requirements of safe, healthy, wholesome, and halal (ASUH) for human consumption and the inner peace of the society.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial agents mainly coliform, i.e., E. coli, S. aureus, Salmonella spp., Campylobacter spp. and Listeria monocytogenes are microbes that potentially contaminate foods, and pose public health threat (Osafo et al 2022;Rafiq et al 2022;Gume et al 2023). The present study was undertaken based on the law of the Republic of Indonesia # 7 of 1996 concerning food that food of animal products must meet the requirements of safe, healthy, wholesome, and halal (ASUH) for human consumption and the inner peace of the society.…”
Section: Discussionmentioning
confidence: 99%
“…This led to studies on milk and milk products to detect LMO to prevent and control its transmission. In this context, LMO has been detected from locally-fermented fresh milk in Nigeria ( Kawo and Bello, 2016 ), traditionally fermented milk in Uganda ( Mugampoza et al, 2011 ), raw milk (from cattle herds) in Nigeria ( Yakubu et al, 2012 ), Botswana ( Morobe, 2009 ), Ethiopia ( Gebretsadik et al, 2011 ; Gume et al, 2023 ), Tanzania ( Msalya, 2017 ), Uganda ( Mugampoza et al, 2011 ) and Algeria ( Hamdi et al, 2007 ), camel milk in Egypt ( Yehia et al, 2016 ), yoghurt in Nigeria ( Kawo and Bello, 2016 ), dairy products in Uganda ( Mugampoza et al, 2011 ) and Algeria ( Hamdi et al, 2007 ), and cheese (cottage and soft) in Botswana ( Morobe, 2009 ), Ethiopia ( Gebretsadik et al, 2011 ) and Nigeria ( Adetunji et al, 2014 ; Table 2 , Figure 3 ). A recently published review on the subject reported a global prevalence of 4.3% in dairy products in Africa with regional variations.…”
Section: Characteristics and Distribution Of Listeriamentioning
confidence: 99%